On simplicity of intermediate -algebras - AMRUTAM, TATTWAMASI; KALANTAR, MEHRDAD (Ergodic theory and dynamical systems, 2020)
We prove simplicity of all intermediate $C^{\ast }$ -algebras $C_{r}^{\ast }(\unicode[STIX]{x1D6E4})\subseteq {\mathcal{B}}\subseteq \unicode[STIX]{x1D6E4}\ltimes _{r}C(X)$ in the case of minimal actions of $C^{\ast }$ -simple groups $\unicode[STIX]{x1D6E4}$ on compact spaces $X$ . For this, we use the notion of stationary states, recently introduced by Hartman and Kalantar [Stationary $C^{\ast }$ -dynamical systems. Preprint , 2017, arXiv:1712.10133 ]. We show that the Powers’ averaging property holds for the reduced crossed product $\unicode[STIX]{x1D6E4}\ltimes _{r}{\mathcal{A}}$ for any action $\unicode[STIX]{x1D6E4}\curvearrowright {\mathcal{A}}$ of a $C^{\ast }$ -simple group $\unicode[STIX]{x1D6E4}$ on a unital $C^{\ast }$ -algebra ${\mathcal{A}}$ , and use it to prove a one-to-one correspondence between stationary states on ${\mathcal{A}}$ and those on $\unicode[STIX]{x1D6E4}\ltimes _{r}{\mathcal{A}}$ .